Related factor with the low weight born in a high-complexity hospital - Acosta Ramírez, José Hernando (Interdisciplinary Journal of Epidemiology and Public Health, 2022)
Background: between the risk factors associated with LBW, adverse social conditions such as unemployment, lack of food security, extreme poverty and barriers to access to health services are reported, and the most frequent causes of low birth weight are preterm births and fetal growth restriction. Objective: To identify the frequency and determinants of low birth weight in a high complexity hospital in Cali Colombia. Methods: Observational analytical study of cases and controls, retrospective. The information of 906 single births and term, that occurred between October and December 2017 was analyzed; We identified 53 cases of low birth weight and compared them with 853 births with normal weight. Results: The exposure variables that showed association with LBW were the OR gestation time 10.2 (CI 95%: 4.7-21.9, p: 0.000); primigestation OR 0.9 (CI 95%: 1.1-3.5; p: 0.022). Conclusion: LBW can be explained by biological variables with a sociodemographic background, specifically primigestation as a risk of LBW in our population.